Combined mTORC1/mTORC2 inhibition blocks growth and induces catastrophic macropinocytosis in cancer cells - Srivastava, Ritesh K. (Proc Natl Acad Sci U S A, 2019)
The mammalian target of rapamycin (mTOR) pathway, which plays a critical role in regulating cellular growth and metabolism, is aberrantly regulated in the pathogenesis of a variety of neoplasms. Here we demonstrate that dual mTORC1/mTORC2 inhibitors OSI-027 and PP242 cause catastrophic macropinocytosis in rhabdomyosarcoma (RMS) cells and cancers of the skin, breast, lung, and cervix, whereas the effects are much less pronounced in immortalized human keratinocytes. Using RMS as a model, we characterize in detail the mechanism of macropinocytosis induction. Macropinosomes are distinct from endocytic vesicles and autophagosomes in that they are single-membrane bound vacuoles formed by projection, ruffling, and contraction of plasma membranes. They are positive for EEA-1 and LAMP-1 and contain watery fluid but not organelles. The vacuoles then merge and rupture, killing the cells. We confirmed the inhibition of mTORC1/mTORC2 as the underpinning mechanism for macropinocytosis. Exposure to rapamycin, an mTORC1 inhibitor, or mTORC2 knockdown alone had little or reduced effect relative to the combination. We further demonstrate that macropinocytosis depends on MKK4 activated by elevated reactive oxygen species. In a murine xenograft model, OSI-027 reduced RMS tumor growth. Molecular characterization of the residual tumors was consistent with the induction of macropinocytosis. Furthermore, relative to the control xenograft tumors, the residual tumors manifested reduced expression of cell proliferation markers and proteins that drive the epithelial mesenchymal transition. These data indicate a role of mTORC2 in regulating tumor growth by macropinocytosis and suggest that dual inhibitors could help block refractory or recurrent RMS and perhaps other neoplasms and other cancer as well.